• Jan 8th 2008, 02:46 AM
ForgottenMemorie
Find the factors of $(4x^2+13x-12)=0$ and use them to solve teh quadratic equation:

$(4x^2+13x-12)=0$

$2x^2+1.6x-1.3=0$

Ive been reading higher engineering mathamatics by John Bird but i still dont get it or know where to start. Help is much apreciated.

If you can break it into steps so i dont egt lost again that would help.
• Jan 8th 2008, 03:53 AM
mr fantastic
Quote:

Originally Posted by ForgottenMemorie
Find the factors of $(4x^2+13x-12)=0$ and use them to solve teh quadratic equation:

$(4x^2+13x-12)=0$

Mr F says: You really must (re-?)learn to factorise.

$(4x^2+13x-12)=0 \Rightarrow 4x^2 + 16x - 3x - 12 = 0$

$\Rightarrow 4x(x + 4) - 3(x + 4) = 0 \Rightarrow (4x - 3)(x + 4) = 0$.

Therefore either 4x - 3 = 0 or x + 4 = 0. Therefore x = .......

$2x^2+1.6x-1.3=0$

Mr F says: Use the quadratic formula (there are probably more websites explaining the quadratic formula and how to use it than you've had hot breakfasts). Or factorise:

$2x^2+1.6x-1.3=0 \Rightarrow 2x^2 - 2.6x + x - 1.3 = 0$

$\Rightarrow 2x(x - 1.3) + 1(x - 1.3) = 0 \Rightarrow (2x + 1)(x - 1.3) = 0$.

Therefore either 2x + 1 = 0 or x - 1.3 = 0. Therefore x = ....

Ive been reading higher engineering mathamatics by John Bird but i still dont get it or know where to start. Help is much apreciated.

Mr F says: Uh huh. The hard fact is that a textbook with that title is gonna be pitching way over your head, bud. You need a maths textbook pitched at high school level. Or google solving quadratic equations and find a website that floats your boat.

If you can break it into steps so i dont egt lost again that would help.

..